The Improving Economic Status of Black Americans. - Smith, James P. (American Economic Review, 1978)
While contemporary rhetoric often highlights differences between races, the data show that blacks are becoming less distinguishable from whites in at least one relevant index of performance-market earnings. Relative to white males, black male earnings have gradually increased, and the rise during the 1960's and the early 1970's is larger than that observed earlier. (See Table 1.) Yet, it is clearly the contrast between white and black females that is extraordinary. Twenty years ago the average black woman employed full time was earning approximately half the wage of a similarly employed white woman. By 1975, almost complete racial parity among women had been achieved. In a recent article (1977), Finis Welch and I argued that the advance in the relative income of black males between 1960 and 1970 was due mainly to converging educational distributions by race and a narrowing in wage differentials between regions. Skill levels were relatively constant within cohorts and convergence was accomplished as increasingly similar racial cohorts entered labor markets while other less similar cohorts retired. Finally our test of affirmative action pressures indicated that before 1970 they had little impact. My first objective is to update our previous research to determine if the events of the last decade for males have continued unabated into the mid1970's. Since a complete understanding of the dynamics of blackwhite changes necessitates explaining the patterns for females, my second goal is to expand the wage comparisons to include women. The major explanations for narrowing in racial wage differences can be placed under four general categories. The central idea of the vintage hypothesis is that more recent black cohorts begin their job experiences with larger initial stocks of human capital, relative to whites, than previous cohorts. The second explanation involves migration. The rural-South to urban-North migration has partly been superceded by southern blacks moving to what are by now economically vibrant southern cities. The third category involves the effects of government affirmative action. Since 1970, it is alleged that a series of court cases imposing severe financial penalties on firms for noncompliance with affirmative action goals have added sharp teeth to government jaw boning. Finally, changes in other aspects of market work may be important in narrowing relative wages. This factor is more relevant for women than men and includes the choice of partor full-time work, unique characteristics of certain occupations, and biases due to limiting comparisons solely to working women.